2013
DOI: 10.1590/s0102-09352013000200013
|View full text |Cite
|
Sign up to set email alerts
|

Hematologia e bioquímica sérica de equinos de concurso completo de equitação em treinamento

Abstract: Avaliaram-se a hematologia e a bioquímica sérica em equinos de concurso completo de equitação (CCE) em treinamento durante testes de esforço incremental em esteira ergométrica de alta velocidade. Foram utilizados 16 equinos em delineamento experimental inteiramente ao acaso com quatro tratamentos e quatro repetições em esquema de parcelas subdivididas, utilizando-se como fontes de variação nos tratamentos a idade e o histórico de treinamento em CCE. As parcelas foram constituídas pelos testes incrementais real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2
3
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
4
2
3
5
Order By: Relevance
“…The high levels of CK and LDH shown in Table 2 were not accompanied by significant increases in serum creatinine. These data corroborate with those observed by Noleto (2012) and Santiago et al (2013), which found no elevation in serum creatinine levels after prolonged exercise. The BUN levels rose from day 4 but remained constant tion, there was a decrease in the serum levels of these cells, and on the15th day, the average was 2600±277 (p<0.0001), as shown in Figure 5.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The high levels of CK and LDH shown in Table 2 were not accompanied by significant increases in serum creatinine. These data corroborate with those observed by Noleto (2012) and Santiago et al (2013), which found no elevation in serum creatinine levels after prolonged exercise. The BUN levels rose from day 4 but remained constant tion, there was a decrease in the serum levels of these cells, and on the15th day, the average was 2600±277 (p<0.0001), as shown in Figure 5.…”
Section: Resultssupporting
confidence: 93%
“…The neutrophil leukocytosis observed in all animals in this study is described in the equine endurance practice and some other modalities (Orozco et al 2006, Ferraz et al 2009, Miranda et al 2011, Santiago et al 2013. The WBC has been widely used as an indicator of stress in horses.…”
Section: Discussionmentioning
confidence: 56%
“…The horses of G1 had higher uric acid concentration than the athletic horses (p < 0.05) in M0. However, in G1, these values remained constant before and after the exercises, in a concentration similar to that reported by Santiago et al (2013) for event horses in training. On the contrary, in the athletes, there was an elevation of uric acid in M1 compared with M0 (p <0.05), indicating that physical exertion during exercise was higher in this group.…”
Section: Resultssupporting
confidence: 86%
“…Além disso, equinos Quarto de Milha possuem alta proporção de fibras musculares do tipo II, importantes para exercícios de alta intensidade e curta duração por terem capacidade de contração rápida e maior potencial glicolítico (Eaton 1998, Hodgson et al 2014. Em resposta ao treinamento, o organismo passa por adaptações fisiológicas que levam a uma diminuição progressiva das concentrações sanguíneas de lactato após o exercício, dentre essas adaptações estão o aumento da capacidade em metabolizar o lactato e o aumento na proporção de fibras IIA:IIX, já que as fibras do tipo IIA possuem melhor capacidade oxidativa ( Santiago et al 2013). Sendo assim, a determinação do lactato após o exercício permite determinar o nível de esforço físico aos quais os equinos foram submetidos, bem como determinar o preparo dos referidos animais para realizar o exercício imposto (Gomide et al 2006).…”
Section: Discussionunclassified
“…Equinos bem condicionados tendem a apresentar melhores taxas de remoção de lactato (Gama et al 2012). O retorno das concentrações sanguíneas de lactato aos valores basais, 30 minutos após a realização do exercício, observado neste trabalho em ambos os grupos pode indicar um efeito positivo do treinamento sobre o condicionamento físico dos animais (Zobba et al 2011, Santiago et al 2013, Assenza et al 2014.…”
Section: Discussionunclassified